2018
DOI: 10.1016/j.canlet.2018.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stem cells with dietary phytochemical - Repositioned drug combinations

Abstract: The tumor microenvironment is complex with the cancer stem cell (CSC) as a member within its community. This population possesses the capacity to self-renew and to cause cellular heterogeneity of the tumor. CSCs are resistant to conventional anti-proliferative drugs. In order to be curative, it is imperative that CSCs must be eliminated by cancer therapy. A variety of dietary phytochemicals and repositioned drugs can act synergistically with conventional anti-cancer agents. In this review, we advocate the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 147 publications
0
26
0
Order By: Relevance
“…Epigallocatechin-gallate (EGCG) is the most abundant (at least 50% of the total catechin content) and the most biologically active catechin present in green tea extracts. Many clinical studies have demonstrated the anti-proliferative, anti-oxidant, and anti-cancer effect of EGCG and, more generally, of a green tea catechins mixture [161], given pure or in combination with other natural compounds [162,163]. Although the anti-tumoral effects of EGCG have clearly been recognized, the molecular mechanism of action of catechins needs more investigation.…”
Section: Catechinsmentioning
confidence: 99%
“…Epigallocatechin-gallate (EGCG) is the most abundant (at least 50% of the total catechin content) and the most biologically active catechin present in green tea extracts. Many clinical studies have demonstrated the anti-proliferative, anti-oxidant, and anti-cancer effect of EGCG and, more generally, of a green tea catechins mixture [161], given pure or in combination with other natural compounds [162,163]. Although the anti-tumoral effects of EGCG have clearly been recognized, the molecular mechanism of action of catechins needs more investigation.…”
Section: Catechinsmentioning
confidence: 99%
“…Curcumin inhibits cancer development and progression by targeting the PI3K/AKT signaling pathway in prostate, lung, breast, and ovarian cancers (Yallapu et al, ; Hamzehzadeh, Atkin, Majeed, Butler, & Sahebkar, ; Jin, Qiao, Wang, Xu, & Shang, ; Wang et al, ; Yallapu et al, ; Yu et al, ). Curcumin has also gained much importance in the recent past due to its potential of targeting CSCs (Chan et al, ; Dandawate et al, ; Subramaniam et al, ).…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%
“…The effectiveness of phytochemicals has also been found promising on cancer stem cells (CSCs) and has gained immense attention in the recent past for their therapeutic potential against drug-resistant cancers by targeting CSCs and associated signaling pathways (Dandawate, Subramaniam, Jensen, & Anant, 2016;Liskova et al, FIGURE 2 Structure of some common phytochemicals 2019; Oh, Hlatky, Jeong, & Kim, 2016;Subramaniam, Kaushik, Dandawate, & Anant, 2018). A combination of dietary phytochemicals and some repositioned drugs (e.g., metformin, niclosamide, and thioridazine) along with conventional chemotherapeutic drugs have been shown to induce synergistic effects in targeting CSCs (Chan, Chen, & Fong, 2018).…”
Section: Cancer Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin (diferuloylmethane) isolated from the dried powder of rhizome of Curcuma longa Linn ( Zingiberaceae ) (Akbar et al, 2018), has been shown to have beneficial properties in vitro and in vivo studies (Akbar et al, 2018; Mokhtari‐Zaer et al, 2018). Curcumin modulates cell growth and inhibits angiogenesis in cancer cells (Fan et al, 2016; Huang et al, 2017; Chan et al, 2018). The anti‐cancer effects of curcumin are mediated partly via down‐regulation of angiogenic factors such as vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), and upregulation of expression of anti‐metastatic proteins and the tissue inhibitor of metalloprotease‐2 (TIMP2).…”
Section: Introductionmentioning
confidence: 99%